Disseminated Streptococcus pneumoniae infection involving a ventricular assist device. Issue 4 (14th July 2015) - Reeves, J.S.; Rajagopalan, N.; Huaman, M.A.
Abstract We describe the first reported case, to our knowledge, of disseminated pneumococcal infection involving a left ventricular assist device (LVAD). The management of this infection was extremely challenging, requiring multiple surgical debridements, LVAD removal, and prolonged courses of antibiotics. The Streptococcus pneumoniae isolate was found to be serotype 19F, which is included in both the pneumococcal polysaccharide and conjugate vaccines. This report highlights the importance of routine screening for up‐to‐date vaccination in patients who undergo LVAD implantation.